2022
DOI: 10.3390/ijms23063300
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Valine and Isoleucine Restores the Growth of Protein-Restricted Pigs Likely through Improved Gut Development, Hepatic IGF-1 Pathway, and Plasma Metabolomic Profile

Abstract: Valine (Val) alone or in combination with isoleucine (Ile) improves the growth under severe protein restriction; however, the underlying mechanisms remain unknown. In this study, we assessed whether Val/Ile-induced growth in protein-restricted pigs is associated with changes in gut development, hepatic insulin-like growth factor 1 (IGF-1) production, and blood metabolomics. Forty piglets were assigned to five dietary groups: positive control (PC) with standard protein content; low protein (LP) with very low pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 69 publications
4
16
0
Order By: Relevance
“…Very low protein diets reduce the total N excretion [ 8 , 9 , 10 ], but they have an adverse effect on growth performance of pigs even when supplemented with FFL [ 11 , 12 , 13 , 14 ]. We and others have shown that supplementing BCAA, Val and a combination of Val and Ile at NRC levels partially improve the growth performance of pigs fed with VLP diets [ 16 , 18 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ]. Little is understood whether a combination of Val above NRC levels and standard amount of Ile will have additive effects on growth of pigs offered VLP diets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very low protein diets reduce the total N excretion [ 8 , 9 , 10 ], but they have an adverse effect on growth performance of pigs even when supplemented with FFL [ 11 , 12 , 13 , 14 ]. We and others have shown that supplementing BCAA, Val and a combination of Val and Ile at NRC levels partially improve the growth performance of pigs fed with VLP diets [ 16 , 18 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ]. Little is understood whether a combination of Val above NRC levels and standard amount of Ile will have additive effects on growth of pigs offered VLP diets.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that supplementation of VLP or SLP diets with BCAA or Val increased the transcript of orexigenic neuropeptide Y and agouti-related protein and decreased the anorexigenic proopiomelanocortin, melanocortin-4-receptor, and cocaine- and amphetamine regulated transcript in hypothalamus, which may contribute to improved FI in BCAA supplemented groups [ 17 , 26 , 38 , 39 ]. We recently showed that Val and Ile combination added at NRC [ 15 ] levels into VLP diets improved the growth performance to the levels seen in pigs received standard protein diet [ 24 ]. The partial, but not complete recovery in growth performance in VA and VAIL groups in this study might be due to AA imbalances resulted from higher ratio of Val:Ile or ratio of Val to other AA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomics has widely been used since the advent of next-generation sequencing technology in pig research. It has been used to identify differences in boar sperm freezability [ 22 ], to identify the complex molecular regulatory network of meat quality in Enshi black pigs [ 23 ] and the growth mechanism of protein-restricted pigs [ 24 ].Thus, the metabolomics is suitable for our study to identify the serum difference between 6 to 12 M Bama miniature pigs.…”
Section: Introductionmentioning
confidence: 99%